The digital interface and new media art installations - Shanbaum, Phaedra (Routledge advances in art and visual studies., 2020)
This book is about the digital interface and its use in interactive new media art installations. It examines the aesthetic aspects of the interface through a theoretical exploration of new media artists, who create, and tactically deploy, digital interfaces in their work in order to question the socio-cultural stakes of a technology that shapes and reshapes relationships between humans and non-humans. In this way, it shows how use of the digital interface provides us with a critical framework for understanding our relationship with technology.